MEMPRAKSISKAN DUALISME ORANG BIJAK DAN ORANG BEBAL MENURUT AMSAL DALAM PENDIDIKAN AGAMA KRISTEN - Murdiyono, Moses; Saputro, Anon Dwi (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2024)
Abstract This article discusses the concept of dualism between the wise and the foolish according to the teachings of Proverbs in the context of Christian Religious Education. This dualism reflects differences in perspectives, behaviors, and values between wise and foolish individuals. Proverbs, as part of the Bible, serves as the primary foundation in detailing the characteristics of both groups. The research method used is a hermeneutic approach to the wisdom genre, specifically focusing coherently on the thematic elements of the Foolish and the Wise in the Book of Proverbs. The research findings indicate that the integration of this dualistic concept in Christian religious education can positively contribute to the development of character and morality. By understanding the distinctions between the wise and the foolish, it is hoped that Christian religious education can make a positive contribution to shaping a generation with strong character and grounded in spiritual values Keywords: Praxis, Dualism, Wise person, Foolish person, Proverbs